THE INFLUENCE OF COMPETENCY DEVELOPMENT AS AN EFFORT TO IMPROVE PERFORMANCE THROUGH ENTITY INDEPENDENCE AS AN INTERVENING VARIABLE IN THE REGIONAL FINANCIAL AND ASSET MANAGEMENT AGENCY OF JEMBER REGENCY - Ferdianingtyas S (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: The purpose of this study is to assess the effect of competency development on employee performance at the Regional Financial and Asset Management Agency (BPKAD) in Jember Regency, considering organizational independence as a mediating variable. Employee competency is vital for ensuring effective and efficient management of financial and asset resources. Moreover, organizational independence acts as a crucial factor linking competency development with employee performance. Method: This research adopts a quantitative methodology through a survey conducted with 50 BPKAD employees in Jember Regency. Data were gathered using questionnaires and analyzed via Pearson's correlation method. Results: The study's findings reveal that competency development has a direct and significant influence on enhancing organizational independence. Additionally, organizational independence has been shown to have a significant impact on employee performance. Novelty: These conclusions emphasize that competency development is a critical strategy for enhancing organizational performance, with organizational independence playing a role in amplifying this effect.